Investigating Intra-Individual Dietary Changes and 14C Ages Using High-Resolution δ13C and δ15N Isotope Ratios and 14C Ages Obtained from Dentine Increments. Issue 4 (2015) - van der Sluis, Laura G; Reimer, Paula J; Lynnerup, Niels
Abstract : Ten medieval permanent teeth were subjected to incremental dentine sectioning and stable isotope analysis to investigate dietary changes in high resolution. In addition to this, eight increments were also selected for radiocarbon measurements to examine possible intra-individual age differences. Results reveal the cessation of weaning, various dietary profiles, and in some cases significantly different 14 C ages obtained from a single tooth. This case study illustrates how 14 C measurements can function as a proxy alongside the commonly used carbon and nitrogen stable isotope values to interpret the diet of past individuals.